Microgrids as a mechanism for improving energy resilience during grid outages: A post COVID-19 case study for hospitals. (November 2022) - Hervás-Zaragoza, Josep; Colmenar-Santos, Antonio; Rosales-Asensio, Enrique; Colmenar-Fernández, Lucía
Abstract: The high number of natural disasters in recent years, combined with the emergence of COVID-19 and the pressure it has exerted on healthcare services, has led to the need to guarantee the power supply to critical infrastructures. In this context, ensuring critical loads of hospital has become a mandatory task. Thus, the aim of the work presented here is to improve the energy resilience of a hospital through the installation of a microgrid consisting of a photovoltaic system working together with a diesel generator in the energy resilience scenario. In the first scenario, it has been evaluated how a microgrid es economically viable for the case where there is no grid outage. In the second scenario, the microgrid has been optimised taking into account both the economic profitability and the ability to withstand a 24-h outage in the month of lowest radiation. The results obtained have shown that the microgrid consisting of a PV system, an energy storage system and a backup diesel generator was able to withstand an average outage time of 72 h, providing the hospital with a net gain of 24 h in terms of energy resilience compared to the business as usual (BaU) and a reduction in utiliy cost of $ 147, 354.